2017
DOI: 10.1002/clc.22781
|View full text |Cite
|
Sign up to set email alerts
|

The shifting paradigm in the treatment of type 2 diabetes mellitus—A cardiologist's perspective

Abstract: In patients with diabetes mellitus, cardiovascular (CV) disease is the leading cause of morbidity and mortality. A multitude of contemporary antidiabetic agents presents different CV safety profiles. Metformin forms the cornerstone agent to reduce CV events. Newer agents, such as glucagon‐like peptide‐1 agonists and sodium‐glucose cotransporter‐2 inhibitors, have appealing CV benefits. Insulin, dipeptidyl peptidase‐4 inhibitors, and sulfonylureas have neutral CV effects. Cardiologists should familiarize themse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Although the quality measures assessed in this study target chronic disease management, they are also directly pertinent to the prevention of cardiovascular events. While diabetes may have been more commonly managed within primary care settings in the past, findings from recent studies of sodium‐glucose co‐transporter 2 (SGLT2) inhibitors and glucagon‐like peptide‐1 (GLP‐1) receptor agonists have shown that these medications reduce the risk of cardiovascular events in high‐risk patients with diabetes . Based on these data, use of these medications is likely to increase among cardiologists, and the coordination between cardiologists and PCPs when initiating and monitoring these medications will be critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the quality measures assessed in this study target chronic disease management, they are also directly pertinent to the prevention of cardiovascular events. While diabetes may have been more commonly managed within primary care settings in the past, findings from recent studies of sodium‐glucose co‐transporter 2 (SGLT2) inhibitors and glucagon‐like peptide‐1 (GLP‐1) receptor agonists have shown that these medications reduce the risk of cardiovascular events in high‐risk patients with diabetes . Based on these data, use of these medications is likely to increase among cardiologists, and the coordination between cardiologists and PCPs when initiating and monitoring these medications will be critical.…”
Section: Discussionmentioning
confidence: 99%
“…While diabetes may have been more commonly managed within primary care settings in the past, findings from recent studies of sodium-glucose co-transporter 2 (SGLT2) inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists have shown that these medications reduce the risk of cardiovascular events in high-risk patients with diabetes. 17,18 Based on these data, use of these medications is likely to increase among cardiologists, and the coordination between cardiologists and PCPs when initiating and monitoring these medications will be critical. Additionally, influenza vaccination reduces the risk of secondary myocardial infarction in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%